2018
DOI: 10.1002/hlca.201800075
|View full text |Cite
|
Sign up to set email alerts
|

Chalcogen‐Bonding Catalysis: From Neutral to Cationic Benzodiselenazole Scaffolds

Abstract: Benzodiselenazoles (BDS) are emerging as privileged structures for chalcogen‐bonding catalysis in the focal point of conformationally immobilized σ holes on strong selenium donors in a neutral scaffold. Whereas much attention has been devoted to work out the advantages of selenium compared to the less polarizable sulfur donors, high expectations concerning bidentate, rigid, and neutral scaffolds have been generated with little experimental support. Here we report design, synthesis and evaluation of the necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 32 publications
0
28
0
1
Order By: Relevance
“…The existence of two regions of depleted electron density, along with deviations from linearity, makes the prediction of ChB interactions more difficult, and the reported experimental results characterizing these interactions designed purely based on crystal engineering principles remain limited. There are few reported examples of heteromeric systems designed based on double chalcogen bonds, for example, bidentate ChBs with benzodiselenazoles, thiophenes, and tellurophenes from Taylor and Matile, bifurcated ChBs with divalent selenium halide from Reid, and single and double chalcogen bond coordination of telluradiazole derivatives towards halides and pyridine by Zibarev and co‐workers . Intermolecular ChBs in pure chalcogenadiazoles and in pure iso‐tellurazole N ‐oxides reported by Vargas‐Baca, chalcogen‐π interactions in divalent organochalcogen liquids reported by Chopra, and the role of ChBs in the organization of chalcogenazolo‐pyridine scaffolds from Biot and Bonifazi provide important further foundations for the current work.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of two regions of depleted electron density, along with deviations from linearity, makes the prediction of ChB interactions more difficult, and the reported experimental results characterizing these interactions designed purely based on crystal engineering principles remain limited. There are few reported examples of heteromeric systems designed based on double chalcogen bonds, for example, bidentate ChBs with benzodiselenazoles, thiophenes, and tellurophenes from Taylor and Matile, bifurcated ChBs with divalent selenium halide from Reid, and single and double chalcogen bond coordination of telluradiazole derivatives towards halides and pyridine by Zibarev and co‐workers . Intermolecular ChBs in pure chalcogenadiazoles and in pure iso‐tellurazole N ‐oxides reported by Vargas‐Baca, chalcogen‐π interactions in divalent organochalcogen liquids reported by Chopra, and the role of ChBs in the organization of chalcogenazolo‐pyridine scaffolds from Biot and Bonifazi provide important further foundations for the current work.…”
Section: Introductionmentioning
confidence: 99%
“…In the following, we answer the question which regioisomer is preferentially formed, show that fast intramolecular rearrangements influence the result, explain why this detailed question is of general interest, and apply the lessons learned to 3-alkyl-1,2diselenolanes. Recent progress with chalcogen bonding research [23] [24] confirmed that this shift of attention from sulfur to selenium is not a simple extension. Because of the longer SeÀ Se and SeÀ C bonds, ring tension from lone pair repulsion and losses of hyperconjugation are less pronounced in 1,2-diselenolanes than in 1,2-dithiolanes.…”
mentioning
confidence: 99%
“…It is worth noticing that establishing strong ChBs requires angles R-Ch···B L close to 180 • , and thus, conformational flexibility of the ChB donor catalyst should increase its catalytic efficiency. In this regard, it is worth noting that, in the compounds so far studied as organocatalysts, the Ch sites are located in a rigid heteroaromatic structure [15][16][17][18][19][20][21]. (1) is located on the elongation of the C-Ch bond; σ-hole (2) is located on the elongation of the C ArF -Ch bond.…”
Section: Discussionmentioning
confidence: 99%
“…Among the applications based on σ-hole interactions in solution, catalysis represents an active research area. While several catalysts acting as XB donor have been described during the last decade [6,13,14], the first examples of ChB-based catalysis have been very recently reported by the groups of Matile [15][16][17][18], Huber [19][20][21], and Wang [22]. Other recent applications of ChB concern anion binding [ 23,24] and transport [25][26][27].…”
Section: Introductionmentioning
confidence: 99%